Role of amino acids in rheumatoid arthritis studied by metabolomics. (22nd March 2017) - He, Min; Harms, Amy C.; van Wijk, Eduard; Wang, Mei; Berger, Ruud; Koval, Slavik; Hankemeier, Thomas; van der Greef, Jan
Abstract: Background: Rheumatoid arthritis (RA) is a complex, chronic autoimmune disease characterized by various inflammatory symptoms, including joint swelling, joint pain, and both structural and functional joint damage. The most commonly used animal model for studying RA is mice with collagen‐induced arthritis (CIA); the wide use of this model is due primarily to many similarities with RA in human patients. Metabolomics is used increasingly in biological studies for diagnosing disease and for predicting and evaluating drug interventions, as a large number of disease‐associated metabolites can be analyzed and interpreted from a biological perspective. Aim: To profile free amino acids and their biogenic metabolites in CIA mice plasma. Method: Ultra‐high‐performance liquid chromatography/tandem mass spectrometry coupled with multiple reaction monitoring (MRM) was used for metabolomics study. Results: Profile of 45 amine metabolites, including free amino acids and their biogenic metabolites in plasma was obtained from CIA mice. We found that the plasma levels of 20 amine metabolites were significantly decreased in the CIA group. Conclusion: The results suggest that a disordered amine response is linked to RA‐associated muscle wasting and energy expenditure.